Perilaku Waspada Stroke Pengidap Hipertensi - Merry Lusiana; Tati Nuryati; Toha Muhaimin; Rizki Edmi Edison (Health and Medical Journal, 2021)
Introduction: Non infectious disease is a major health problem especially in developing countries. Among those, stroke always be the leading one that occurs followed by health burden.  Some factors in increasing of mortality and disability due to stroke are lack of understanding of risk factors and awareness to early signs especially among people with hypertension. If the factors those influence the knowledge, awareness, and others stroke alert behaviors are known, promotive or prevention acts could be done by health workers. Aims: The aim of this study is to find out the stroke alert behavior among them that conducted at Puskesmas Cengkareng of West Jakarta on July and August 2020. Method: 116 patients were participated to fill the questionnaire and analyzed with cross-sectional design. Results: Our study revealed that knowledge, perception of utility, and perception to level of disease severity is the most influenced factor to stroke alert behavior.